Reformulating the Concept of Mafq?d in Islamic Law and Its Implications for Loss-Related Phenomena in the Modern Digital Era - Harahap, Fahrizal; Hakim, Fiqhan; Hakim, Rizal; Basri, Muhammad; Marjelino, Rino (Yayasan Literasi Kita Indonesia, 2025)
This study revisits the classical Islamic legal concept of mafq?d by situating it within the realities of a modern society increasingly dependent on digital systems. In traditional fiqh, mafq?d refers to a person who is physically missing and whose whereabouts cannot be verified, a condition that carries significant legal implications regarding marriage, inheritance, and personal civil status. However, technological developments in the contemporary era have introduced new forms of “loss” previously unknown in classical literature—such as the disappearance of personal data, the erasure of digital identity traces, system failures that result in loss of access, and the sudden vanishing of a person’s online accounts or profiles without clear cause. These emerging phenomena call for a re-examination of the foundational principles of mafq?d to make them more relevant and adaptable to digital contexts.This research employs a library study approach, utilizing primary Islamic legal sources including works of the classical jurists, texts of u??l al-fiqh, and comparative fiqh literature. These are analyzed alongside contemporary studies on technology law, data protection, and the notion of digital identity. The analysis shows that although classical fiqh does not explicitly address digital forms of loss, several underlying principles hold strong potential for contextual reinterpretation. Doctrines such as precaution (i?tiy??), the elimination of harm, the protection of individual rights, and legal determinations based on public interest (ma?la?ah) provide a methodological basis for extending the concept of mafq?d into digital realms. Through this approach, digital loss is not treated as a direct analogue of physical disappearance, but as a phenomenon that likewise generates uncertainty, impedes the fulfillment of rights, or disrupts the legal status of a person or digital asset.